The Role of Artificial Intelligence in the Academic Work of Preservice Teachers - Haley M Olson; Emily Cline (The Advocate, 2025)
The integration of artificial intelligence (AI) into higher education has rapidly transformed the learning environment, with significant implications for pre-service teacher education. AI tools such as adaptive learning platforms and virtual simulations offer opportunities to enhance instructional design and develop essential teaching competencies. At the same time, challenges related to data privacy and equitable access underscore the need for careful implementation. This study examined pre-service teachers’ use of AI in education methods courses, with the dual aim of understanding their perceptions of AI’s impact on learning and exploring the relationship between academic and everyday AI use. Participants completed the EDUCAUSE AI Landscape Study Survey Instrument (Robert, 2024). Descriptive and correlational analyses revealed that while a majority of students reported limited AI use, a strong positive relationship was found between AI use in academic and everyday contexts. These findings suggest that educator preparation programs carry important implications for redesigning teacher education curricula to prepare future educators for AI-rich classroom environments while maintaining high standards of academic integrity.
Keywords: artificial intelligence; pre-service teacher education; higher education; AI integration